Potential therapeutic use of millet with broad spectrum anticancer properties: current trends and prospects - Anusree Giri; Samima Sultana; Ananya Roy; Debabrata Ray; Indrakshi Barui; Samadrita Sengupta (Discover Food)
Abstract Major, minor, and pseudomillet have a variety of bioactive components that have been promoted, including their potential to manage and prevent cancer. Nevertheless, the effects of millets and millet-based food products containing millet on cancer have not received enough attention. This research note describes a systematic-narrative hybrid method that can be used in a literature review paper to gather information about the effects of consuming millet on cancer prevention, including the bioactive compound in millet that fights cancer and different techniques for elucidating the anti-cancer potential of millet. The method prevents the reader from being overwhelmed with excessive information. The result showed that according to the findings of forty-nine investigations, phytochemicals, polyphenols, flavonoids, carotenoids, fibers, probiotics, and prebiotics are the main bioactive components of millet. Plant-based compounds inhibit cancer growth by suppressing mutations, enhancing apoptosis, managing redox signaling, preventing cell division, halting metastasis, lowering oxidative stress, and influencing neovascularization. Moreover, food products made from millet, such as bakery, confectionery, dairy, and extruded food items, have been shown to have anticancer properties. Even though some millet includes allergies, it does have cancer-fighting compounds. However, interestingly, millet also lessens negative effects brought on by chemotherapy. Suitable millet protein-based delivery systems are therefore desperately needed to improve millet's bioavailability, particularly for cancer patients. Nutrition is crucial in cancer treatment, and further research should focus on implementing optimal millet-based nutrition strategies, including supplementing nutritious foods for those unable to obtain them.